The (truly) first fossil freshwater molluscs from Antarctica - Martínez, Sergio; Scasso, Roberto Adrian; Elgorriaga, Andres; Capelli, Ignacio Andrés; del Valle, Rodolfo; Puerta, Pablo; Lirio, Juan Manuel; Rodriguez Amenabar, Cecilia (PalZ)
New collection work in Mount Flora, Hope Bay, Antarctic Peninsula, has confirmed the presence of bivalve moulds in the Jurassic Mount Flora Formation. In contrast to a twenty-first century article claiming to report the first discovery of fossil freshwater molluscs in Antarctica, evidence of these molluscs was first reported for Antarctica more than 110 years ago by J. Gunnar Andersson. The bivalve was formally described and named some 50 years later, by Camacho, as Antediplodon esperanzaensis. The species was subsequently transferred to the genus Diplodon for unknown reasons. Here, we illustrate specimens from the same locality for the first time with photographs, considering them Unionida incertae saedis, in view of the absence of diagnostic characters. In fact, two morphotypes are present, one elongated, very similar to the nominal species A. esperanzaensis, and another one subelliptical in shape. Fil: Martínez, Sergio. Universidad de la República; Uruguay Fil: Scasso, Roberto Adrian. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires; Argentina Fil: Elgorriaga, Andres. Museo Paleontológico Egidio Feruglio; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Capelli, Ignacio Andrés. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires; Argentina Fil: del Valle, Rodolfo. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; ...